Polysaccharide-reinforced amyloid fibril hydrogels and aerogels. Issue 29 (15th July 2021) - Usuelli, Mattia; Germerdonk, Till; Cao, Yiping; Peydayesh, Mohammad; Bagnani, Massimo; Handschin, Stephan; Nyström, Gustav; Mezzenga, Raffaele
Abstract : The inclusion of low-acetylated Gellan Gum and κ-carrageenan into amyloid fibril gels reinforces them mechanically, while preserving the surface functionality of the amyloid fibrils. Abstract : β-Lactoglobulin amyloid fibrils are bio-colloids of high interest in many fields ( e.g. water purification, cell growth, drug delivery and sensing). While the mechanical properties of pure amyloid fibril gels meet the needs of some applications, mechanical fragility often hinders a wider usage basin. In this work, we present a simple and sustainable approach for reinforcing amyloid fibril hydrogels and aerogels, upon the diffusion of polysaccharides (low-acetylated Gellan Gum and κ-carrageenan) inside their mesh. The formed hybrid materials show enhanced resistance upon compression, without any loss of the exquisite surface reactivity of the amyloid fibrils. The proposed approach can pave the way for designing composite materials that are both highly functional and environmentally friendly.